Artificial beings : the conscience of a conscious machine - Pitrat, J. (Jacques) (ISTE., 2009)
This book demonstrates that not only is it possible to create entities with both consciousness and conscience, but that those entities demonstrate them in ways different from our own, thereby showing a new kind of consciousness.